Prevention of estradiol 17β-d-glucuronide– induced canalicular transporter internalization by hormonal modulation of cAMP in rat hepatocytes - Zucchetti, Andrés Ernesto (2011)
In estradiol 17β-d-glucuronide (E17G)–induced cholestasis, the canalicular hepatocellular transporters bile salt export pump (Abcb11) and multidrug-resistance associated protein 2 (Abcc2) undergo endocytic internalization. cAMP stimulates the trafficking of transporter-containing vesicles to the apical membrane and is able to prevent internalization of these transporters in estrogen-induced cholestasis. Hepatocyte levels of cAMP are regulated by hormones such as glucagon and adrenaline (via the β2 receptor). We analyzed the effects of glucagon and salbutamol (a β2 adrenergic agonist) on function and localization of Abcb11 and Abcc2 in isolated rat hepatocyte couplets exposed to E17G and compared the mechanistic bases of their effects. Glucagon and salbutamol partially prevented the impairment in Abcb11 and Abcc2 transport capacity. E17G also induced endocytic internalization of Abcb11 and Abcc2, which partially colocalized with the endosomal marker Rab11a. This effect was completely prevented by salbutamol, whereas some transporter-containing vesicles remained internalized and mainly colocalizing with Rab11a in the perinuclear region after incubation with glucagon. Glucagon prevention was dependent on cAMP-dependent protein kinase (PKA) and independent of exchange proteins activated directly by cAMP (Epac) and microtubules. In contrast, salbutamol prevention was PKA independent and Epac/MEK and microtubule dependent. Anticholestatic effects of glucagon and salbutamol were additive in nature. Our results show that increases in cAMP could activate different anticholestatic signaling pathways, depending on the hormonal mediator involved.